Developing the administrative creativity of high school leaders in Khamis Mushait governorate in the light of creative leadership - Al Shahrani, Hanan Safar (Journal of Educational and Psychological Sciences, 2018)
The aim of this research was to clarify the importance of administrative creativity and creative leadership in secondary schools, to identify the reality of creative management in secondary schools and to the interrelationship between creative leadership and administrative creativity, and also to contribute to the study of obstacles and obstacles that limit administrative achievement in Khamis Mushait governorate, The research was based on descriptive analytical methodology for its relevance to the subject of research and research objectives in light of the nature of the research problem and the type of variables. Based on the nature of the data to be collected, and the methodology used in the research, the researcher used the questionnaire. The most important research results related to the characteristics of the research community: 86 of the research members represented 86.9% of the total members of the research community. The results showed that (45) members of the research community (45.5%) of the total members of the research community, the number of years of experience (from 10 years to less than 15 years). The results also showed that members of the research community strongly agree with the reality of administrative creativity in the leadership of secondary schools in Khamis Mushait governorate in the light of creative leadership. This axis included nine terms. It was found that members of the research community are very much in agreement with five phrases related to reality Administrative creativity in high school leaders.
Keywords: leadership; creativity; creative leadership; secondary stage